DIALEK ‘AMMIYYAH DALAM PENGAJARAN BAHASA ARAB UNTUK PARIWISATA DI INDONESIA - Misran Misran (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
This work investigates needs of informal dialect (`ammiyyah) in teaching Arabic in Indonesia, especially for tourism industry. The study is based on needs analysis, focusing on necessities and lacks by Waters (1987). By observation, the result shows that both of formal dialect (MSA) and informal dialect are necessary to learn in Arabic for tourism purposes (ASP), by special attention to Gulf Arabic and Egyptian Arabic. In other side, some of lacks is found which include non-language factors, such as education rules, subjects needed, and language factors, such as usage area. However, as long as the aim to be able to communicate in Arabic is reached, both of formal and informal dialects are though.